A systematic archaeological survey in the environs of Khaytabad Tepa (Southern Uzbekistan). Preliminary report on the 2021 pilot season - Jakub Havlík; Ján Bobik; Vendula Dědková; Kateřina Dontová; Jan Krčál; Jana Matznerová; Elena Paralovo; Razieh Taasob; Kahramon Toshaliyev; Jan Ždimera; Shapulat Shaydullaev (Studia Hercynia, 2022)
Tepa sites have oÁen been the focus of archaeological investigations in the lowland areas of Soviet and post- -Soviet Central Asia. is bias frequently led to paying only a lile aention to the surrounding landscape and its potential for the study of historical selement and land use. Moreover, in these environs archaeologists face particularly unfavourable conditions in the landscape, which has been radically transformed by decades of mechanised agriculture and selement growth. e newly launched project of the Czech-Uzbekistani Archaeological Mission aims to answer the challenges of research in the heavily exploited lowlands of southern Uzbekistan and explore the surroundings, supposedly an economic territory, of Khaytabad Tepa, a walled selement occupied between the Achaemenid period and the Middle Ages. For the investigation of various parts of a culturally and physically diverse landscape (village areas, fields, tepa mounds), a flexible methodology was developed, building on an intensive surface survey as the dominant research component to analyse the Khaytabad Tepa surroundings. Given the initial stage of the research, this report focuses on the background, objectives, and methodology of the project and evaluates the 2021 pilot season. e amount and chronological range of collected material point to the great potential of the adopted approach as well as the research area itself. e identified artefact scaers indicate a substantially more complex selement development than has been acknowledged so far: e collected poery assemblages largely correspond to the occupation timespan of the central walled selement. e widespread distribution of Iron Age and Middle Ages material suggests an extensive exploitation of the area in these particular periods.